The relationship between social support and work life balance in private organization - Ting, Shirley; Dayang Kartini, Abang Ibrahim (-, 2012)
This study aims to determine the relationship between social support and work life balance among married employees. The study was conducted in private organization located at Kuching, Sarawak. This study used quantitative method and five Likert-scale questionnaires were distributed to the respondents. A total of 60 set of survey questionnaires were usable for this study. The data that collected were analyzed using the SPSS version of 17.0. Pearson Correlation Analysis used to identify the relationship between spouse, family members, supervisor, and colleague with work life balance. The finding in this study showed that there was no significant relationship between spouse (r=0.222) and work life balance. However, finding showed that there were significant relationship between family members (r=0.523**), supervisor (r=0.511**) and colleague (r=0.388**) with work life balance. Based on these findings, contributions and recommendations for organization, human resource practitioner and future researchers were also discussed further.